A Closer Examination of the ‘Abundant-Center’ for Ectomycorrhizal Fungal Community Associated With Picea crassifolia in China - Wang, Xiaobing; Han, Qisheng (Frontiers in Plant Science, 2022)
A long-standing hypothesis in biogeography predicts that a species’ abundance is highest at the centre of its geographical range and decreases toward its edges. Here, we test the abundant-centre hypothesis of ectomycorrhizal (ECM) fungal communities associated with Picea crassifolia, an endemic species widely distributed in northwest China. We analyzed the taxonomic richness and the relative abundance of ECM fungi in four main distribution areas, from centre to edges. In total, 234 species of ECM fungi were detected, and of these, 137 species were shared among all four sites. Inocybe, Sebacina, Tomentella and Cortinarius were the dominant genera. ECM fungal richness and biodiversity was highest at the central and lower in peripheral sites. Our results indicated that ECM fungal species richness consistent with the abundant-centre hypothesis, while the relative abundances of individual fungal genera shifted inconsistently across the plant’s range.